Survey on some important functional foods from the Chinese and Eastern perspective - Shahrajabian, Mohamad Hesam; Sun, Wenli; Cheng, Qi (Polish Journal of Agronomy, 2020)
The functional food industry has been developing rap-idly in recent years. The most important pharmacological prop-erties of jujube are anti-diabetic effects, hypnotic-sedative and anxiolytic effect, neuroprotective activity, sweetness inhibitor, anti-cancer activity, antimicrobial activity, anti-ulcer activity, an-ti-inflammatory and anti-spastic effect, anti-allergic activity, per-meability enhancement activity, cognitive activities, anti-fertility property, hypotensive and anti-nephritic effect, cardiovascular ac-tivity, immunostimulant effects, anti-oxidant effects, and wound healing activity. N. nucifera has various notable pharmacological activities such as anti-ischemic, antioxidant, anti-cancer, antivi-ral, antiobesity, lipolytic, hypocholestermic, antipyretic, hepato-protective, hypoglycaemic, antidiarrhoeal, antifungal, antibacte-rial, anti-inflammatory and diuretic activities. Coix is a source of ornamental beads, a stable sustenance, and a productive fodder grass increasingly viewed as a potential energy source. The heal-ing properties of lily include moisturizing the lungs, relieving cough from lung-dryness, clears heart-fire and tranquilizes the mind. Dried lily bulbs are commonly used in herbal formulas for promoting lung health, treating yin-deficiency of the heart which manifests as irritability, insomnia, dreaminess, palpitation and absent-mindedness, and promotes vital fluid and improves skin complexion. The most important tremella mushroom benefits are anti-aging, anti-inflammatory, lower cholesterol, combat obesity, protect nerves and may fight cancer. Functional foods are making inroads into Chinese diets with their promises to improve health and nutrition. Chinese consumers should choose nutritional and healthy food to maintain general health and reduce the risk of health problems.